206: Intranasal Fentanyl and Midazolam Use in a Pediatric Emergency Department. Issue 6 (1st June 2014) - Foster, M; Cox, K
Abstract: BACKGROUND: Intranasal (IN) delivery is a fast and effective administration route for several medications. We recently implemented IN use of fentanyl and midazolam in the emergency department (ED) for pain control and anxiolysis during short term procedures in pediatric patients with no intravenous (IV) access. OBJECTIVES: This review identifies indications for IN medication use, dosing, adverse effects, and patient/family/staff satisfaction. DESIGN/METHODS: Patients who received IN fentanyl or midazolam in the ED between April 1st–June 1st, 2011 were identified utilizing computerized physician order entry (CPOE) and electronic medical record (EMR) data. Patient age, indication for medication, dose received, adverse effects, and discharge status were evaluated. ED staff satisfaction and patient and family satisfaction with IN medication delivery versus alternative methods were evaluated through anonymous surveys. RESULTS: A total of 102 patients were identified during the two-month study period. The most common indications for IN fentanyl and/or mid-azolam were to provide pain control and/or anxiolysis during abscess incision and drainage, laceration repair, IV and Foley catheter insertion. All patients receiving IN midazolam were pretreated with buffered lidocaine 1% 0.5 to 1 ml IN to prevent nasal burning associated with the concentrated (5 mg/ml) midazolam product. Midazolam demonstrated to be safe and effective at 0.2 to 0.5 mg/kg/dose (maximum dose 15 mg) and fentanyl at 2 to 5 mcg/kg/dose (maximum dose 200 mcg). The most common doses utilized were midazolam 0.3 mg/kg and fentanyl 3 mcg/kg. The majority of patients received a combination of fentanyl and midazolam, versus fentanyl or midazolam alone. Adverse effects included rash in one patient, which resolved with oral diphenhydramine, and paradoxical agitation to midazolam in one patient, which resolved with no intervention. No patients required hospital admission due to adverse effects. The majority of patients were discharged home with no complications and positive experiences, according to ED staff, patient, and family satisfaction surveys. CONCLUSIONS: IN fentanyl and midazolam are advantageous alternatives to oral or intramuscular (IM) pain or anxiolysis medications, particularly in the ED. With a fast onset, short duration of action, and demonstrated safety and effectiveness for pain control and/or anxiolysis, many short procedures or exams can be performed effectively and quickly without waiting for the delayed onset of action of oral or IM medications.